Zero-gap type cation exchange membrane method salt electrolysis cell
By using the combined structure of extended metal and plain zinc mesh in electrolyte membrane electrolysis, the problem of uneven resistance and current distribution of electrolyte membrane is solved, and a low electrolyte voltage and high energy-efficient electrolytic effect is achieved.
Patent Information
- Application Number
- JP2024043605
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-03-19
AI Technical Summary
The prior art is difficult to effectively reduce the resistance of the electrolyte membrane itself in the zero-gap method, resulting in large loss of electrolyte voltage and difficulty in optimizing the electrode structure to uniformly distribute the current density.
The extended metal is used as the electrode matrix of the -roll pressed product, and combined with the plain-wall zinc mesh as the cathode, the opening period of the cathode is set to 1/2 or less of the short-side opening period of the cathode. This structure ensures that the current is evenly distributed on the surface of the electrolyte membrane.
Operation of extremely low electrolyte voltage in chloralkaline electrolysis is achieved, significantly reducing the energy consumption of the electrolysis process and extending the service life of the electrode.
Smart Images

Figure 0007654291000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to electrolysis that enables electrolysis with minimal power consumption in a zero-gap type cation exchange membrane method for electrolyzing saline water to obtain chlorine from the anode and hydrogen and sodium hydroxide from the cathode. [Background technology]
[0002] At present, the cation exchange membrane method is commonly used in chloralkali electrolysis. Moreover, in order to minimize the electrical resistance in the electrolysis, the so-called zero gap method, in which the anode and cathode are in close contact with a cation exchange membrane (a diaphragm), is widely used.
[0003] In the early days of cation exchange membrane salt electrolysis, there were problems with the quality of the cation exchange membrane itself. The anode side of the cation exchange membrane would become strongly alkaline due to the return of alkali from the cathode chamber. This would result in a decrease in the efficiency of chlorine generation at the anode and corrosion of the titanium base material that constitutes the anode due to alkali. To avoid this, measures such as inserting a PTFE mesh between the anode and the cation exchange membrane were taken to avoid contact between the anode and the cation exchange membrane.
[0004] Later, with the improvement and development of cation exchange membranes, especially when carboxylic acid membranes were put to practical use in place of the conventional sulfonic acid membranes, the problem of alkali returning to the anode side was solved, and there were no problems even if the anode was in contact with the cation exchange membrane, and the electrical resistance of the electrolyte due to the close contact between the anode and the cation exchange membrane was reduced, and a drop in voltage was achieved.Note that nowadays, a composite membrane has been used, and the cathode is also in close contact with the cation exchange membrane for electrolysis, and with the implementation of the zero gap method, it has become possible to operate at a lower electrolysis voltage.
[0005] However, in the case of conventional electrolytic cells, in addition to the pressure from the cathode side to the anode side through the cation exchange membrane due to the difference in specific gravity between the caustic alkali serving as the cathode electrolyte and the saline solution serving as the anolyte, pressure fluctuations caused by air bubbles generated within the electrolytic cell require the anode itself to have great physical strength, and optimization of the shape itself has been difficult.
[0006] On the other hand, on the cathode side, which is hardly affected by pressure fluctuations, even if the anode, cation exchange membrane, and cathode are initially in close contact with each other, the cation exchange membrane is pushed toward the anode by the caustic soda solution, which is the catholyte, and the cathode and cation exchange membrane become separated, making it difficult to achieve a completely zero gap.
[0007] Subsequently, improvements were made to the electrolytic cell to eliminate pressure fluctuations within the cell, and special processing was carried out to make the surface of the cation exchange membrane hydrophilic, resulting in so-called zero-gap electrolysis, which minimizes the liquid resistance caused by the electrolyte; in other words, the cathode surface is pressed against the cation exchange membrane so that the anode and cathode are always in contact with the surface of the cation exchange membrane, resulting in close contact with the cation exchange membrane.
[0008] There is a technique for making a perforated plate into an electrode plate in which the perimeter of the hole portion is specified as 2 m or more for an effective flat electrode plate unit size of 100 x 100 mm (see, for example, Patent Document 1).
[0009] There is a technology that uses an expanded metal with a thickness of 0.05 mm to 0.3 mm as the anode (for example, see Patent Document 2). It has been shown that by using such a thin anode and placing the anode as close as possible to the cation exchange membrane, it is possible to operate at a low voltage.
[0010] There is a technology for electrolysis using the zero gap method in which the expanded metal anode is completely smoothed to the thickness of the original plate so that it adheres closely to the cation exchange membrane (see, for example, Patent Document 3). This reduces the electrolysis voltage by bringing the anode into almost close contact with the cation exchange membrane.
[0011] There is a technology that uses an electrode structure made of expanded metal that is very thin, has small pores, and has an extremely small aperture ratio (see, for example, Patent Document 4). In this technology, the plate thickness is 0.5 to 1.2 mm, which is close to the electrode base material that is commonly used today.
[0012] There is a technology in which an expanded metal is used as the anode, the plate thickness is 0.1 to 0.5 mm, and the shape of the formed mesh is SW / LW = 0.45 to 0.55 (see, for example, Patent Document 5). It has a relatively large mesh opening, but the plate thickness of the mesh used is thin.
[0013] Regarding water electrolysis cells, there is a technique in which a partition wall is provided with projections and recesses, and electrodes are fitted to the projections and recesses, and a cushion mat is used as an elastic body to hold down the electrodes (see, for example, Patent Document 6).
[0014] Regarding water electrolysis, there is a technology that uses a metal wire mesh containing nickel as the cathode and forms an electrode active material on its surface (see, for example, Patent Document 7). The mesh size is disclosed as being 0.05 mm or more and 1.0 mm or less in wire diameter, and a plain weave of 20 to 60 meshes. Expanded metal is described as the anode, and it is shown that it is zero gap in particular in relation to the diaphragm and cation exchange membrane. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] Japanese Patent Application Publication No. 56-146884 [Patent Document 2] Japanese Patent Application Publication No. 58-130286 [Patent Document 3] Japanese Patent No. 4453973 [Patent Document 4] WO2018 / 131519 publication [Patent Document 5] WO2015 / 108115 publication [Patent Document 6] Japanese Patent No. 7323299 [Patent Document 7] WO2018 / 151228 publication Summary of the Invention [Problem to be solved by the invention]
[0016] This zero-gap method makes it possible to minimize the electrical resistance of the electrolyte between the anode and cathode, but there has been little discussion on the reduction of the electrical resistance of the cation exchange membrane itself, which is only about 0.1 to 0.2 mm thick and has a voltage loss of 200 mV or more. To reduce the electrical resistance of the cation exchange membrane, it is necessary to make the current value flowing across the entire membrane surface the same and to make the current density in the cation exchange membrane uniform, since the membrane resistance itself does not change. To achieve this, it is usually necessary to specify the relationship between the mutual shapes of the anode and cathode sandwiching the cation exchange membrane. However, although various anode and cathode structures have been examined, no prior literature that can directly refer to the relationship in size and shape between the anode and cathode facing each other across the cation exchange membrane has been found.
[0017] As for the anode and cathode, the shape of the anode is indeed made finer, and a fine electrode structure is given to make the current density in the cation exchange membrane uniform. However, in reality, specifying the electrode shape, including removing the air bubbles that are generated, is a big problem.
[0018] Patent Document 1 does not show the shape of the perforated plate. This would mean that a plate with cuts could be used as the substrate, but in that case, the gas generated on the cation exchange membrane side would have nowhere to escape. Therefore, the technology includes a technology that makes it impossible to maintain a low voltage.
[0019] Regarding Patent Document 2, although the operating conditions may be different from the present, when the actual electrode area is taken into consideration, it is clear that the electrode area of the cross section due to the thinness of the plate is small and is completely incompatible with the present electrolysis conditions that require high current density. Also, it is presumed that if there is no physical protection on the back side of the anode, the anode will be easily deformed by pressure from the cathode chamber side.
[0020] In Patent Document 4, there is a restriction on the relationship between the opening rate and the mesh size of the expanded metal, and applying this restriction results in a small mesh size. This makes it difficult to vent the gas generated on the cation exchange membrane side of the anode to the back side of the anode, except under special conditions, and at the same time, there is a possibility that the supply of electrolyte to this part will be insufficient, which is problematic.
[0021] In Patent Document 5, the thin thickness of the expanded metal plate allows the gas generated on the electrolytic surface in contact with the cation exchange membrane to escape relatively well to the side opposite the cation exchange membrane of the electrode, i.e., the back side of the electrode, but the thin thickness of the expanded metal plate inevitably reduces the electrode surface area in three dimensions, increasing the current density on the electrode surface, which may increase the electrode potential and shorten the electrode life, which is problematic, especially for high current densities.
[0022] Patent Document 6 does not describe the combination of a cathode and an anode, but describes only the cathode. Although there is no indication of the cathode, a plain woven mesh is suggested as the cathode, and it is preferable that the wire diameter is 0.05 mm or more and 1.0 mm or less, and the mesh number is 5 to 70, which is an extremely wide range. There is no description of how such a cathode should be related to the anode and the cation exchange membrane.
[0023] In Patent Document 7, the shapes of the anode and cathode are described as expanded metal and plain woven mesh, but the relationship between their sizes is not disclosed at all.
[0024] In other words, in the past, much effort was made to reduce the electrical resistance of the electrolyte, which has a relatively high electrical resistance. However, another component with a large electrical resistance is the cation exchange membrane itself, which has an apparent thickness of only about 100 microns but is unable to withstand the commonly used electrolysis current density of 0.5 A / cm. 2Even at this level, it is said that there is an electrical resistance of about 0.2 V or more. In this situation, the basic technology for achieving the so-called zero gap is widely known, but the technology for the relationship between the electrodes and the cation exchange membrane is almost unknown. This is probably because, in order to solve the problems of air bubble generation and liquid resistance at the anode and cathode, the anode and the cathode have been considered in relation to the cation exchange membrane that they are in close contact with, and little consideration has been given to the relationship between the anode and the cathode, focusing on the cation exchange membrane, that is, the problem of electrical resistance within the cation exchange membrane.
[0025] Thus, in the technology of alkaline water electrolysis as salt water electrolysis or similar electrolysis, when an expanded metal is used as the anode and a plain woven mesh made by knitting nickel or a metal wire containing nickel is used as the cathode, the relationship between the shape of the anode and the shape of the cathode and the combination of these has never been considered. Furthermore, the ultimate reduction in electrolysis voltage depends on how to reduce the electrical resistance when the cation exchange membrane is sandwiched between the cathode and anode in a zero-gap type, and a measure for this is needed.
[0026] Therefore, an object of the present disclosure is to provide an electrolytic cell that can be operated at an exceptionally low electrolysis voltage and has a significant power saving effect, in a cation exchange membrane electrolysis cell that can obtain high-purity caustic alkali in so-called chloralkali electrolysis, in which saline solution is electrolyzed to obtain sodium hydroxide and chlorine, and that uses the cation exchange membrane method. [Means for solving the problem]
[0027] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by (1) forming an expanded metal into a roll-pressed product as an anode and then using it as an electrode base material, and in this case, performing roll pressing so that the apparent thickness of the roll-pressed product is not thinned to the thickness of the sheet (hereinafter also referred to as the original sheet) before processing of the expanded metal (hereinafter, a roll-pressed product that satisfies this condition is also referred to as a weakly pressed product), (2) using a plain woven nickel mesh as the cathode, and (3) further setting the pitch of the cathode to 1 / 2 or less of the SW of the anode, thereby completing the present invention. That is, the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention comprises a cation exchange membrane serving as a diaphragm, an anode in close contact with one surface of the cation exchange membrane, an anode chamber in which the anode is housed and filled with anolyte, a cathode in close contact with the other surface of the cation exchange membrane, and a cathode chamber in which the cathode is housed and filled with catholyte, and in this zero-gap type cation exchange membrane process sodium chloride electrolysis cell in which anode gas is generated at the anode and hydrogen is generated at the cathode, The electrode substrate comprises an electrode base material made of a perforated plate, and an anode coating layer of a hydrophilic electrode active material formed on the surface of the electrode base material, the electrode base material being a roll-pressed product of an expanded metal having a plate thickness of the perforated plate of t mm, an opening period of the long side of the expanded metal being LW mm, an opening period of the short side of the expanded metal being SW mm, and a strand of W mm, the opening ratio of the expanded metal being 20% or more and 60% or less, and the ratio calculated by LW / SW being 1.5 or more and 3.5 or less, and the plate thickness t of the perforated plate being 0.5 mm or more. 0.8 The opening period SW of the short side is 2.0 mm or more and 5.5 mm or less, the apparent thickness Pmm of the roll-pressed product is 1.1t or more and 2.0t or less, and the cathode has a wire diameter of 0.06 to 0.14 The present invention has a nickel mesh formed by plain weaving nickel wires of 1 mm, and a cathode coating layer of a hydrophilic electrode active material formed on the surface of the nickel mesh, and the pitch of the cathode is 1 / 100 of the SW of the anode. (0.64 / 2.2) or higher The zero-gap type cation exchange membrane process saline electrolysis cell is characterized in that it has an elastic body that applies pressure to the surface of the cathode opposite the surface that is in close contact with the cation exchange membrane.
[0028] The zero-gap type cation exchange membrane process chlor-alkali electrolytic cell according to the present invention includes an electrolytic cell in which the expanded metal is made of pure titanium, the anolyte is a saline solution, the catholyte is a caustic soda aqueous solution, chlorine gas is produced as the anode gas, and caustic soda and hydrogen are produced in the cathode chamber.
[0029] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, it is preferable that the expanded metal is made of pure titanium, and the electrode active material of the anode coating layer is a hydrophilic composite oxide containing iridium, ruthenium, and titanium.
[0030] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, the electrode active material of the cathode coating layer preferably contains a platinum group metal and / or a platinum group metal oxide.
[0031] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, the electrode active material of the cathode coating layer preferably contains a composite oxide of ruthenium and cerium.
[0032] In the zero-gap type cation exchange membrane process sodium chloride electrolytic cell according to the present invention, the pitch of the nickel mesh is preferably 0.6 to 1.2 mm.
[0033] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, it is preferable that the elastic body is a sponge-like mattress made of nickel wires randomly folded and bundled, and is placed between the current collector and the cathode. In the zero-gap type cation exchange membrane process saline electrolysis cell according to the present invention, it is preferable that the anode further has an anode coating layer made of a hydrophobic electrode active material between the surface of the electrode substrate and the anode coating layer made of the hydrophilic electrode active material. Effect of the Invention
[0034] According to the present disclosure, it is possible to provide a cation exchange membrane type electrolytic cell which enables extremely high energy savings by minimizing the electrolysis voltage when mainly producing chlorine gas from the anode side and hydrogen and alkali hydroxide from the cathode side. [Brief description of the drawings]
[0035] [Figure 1] 1A and 1B are schematic diagrams showing an example of the shape of an expanded metal, in which (a) shows the shape of an eye, and (b) is a schematic cross-sectional view of a bond taken along line A'. [Diagram 2] 1 is a schematic diagram showing the mesh shapes of expanded metal, where (a) shows a diamond shape and (b) shows a tortoise shell shape. [Diagram 3] 1A and 1B are diagrams illustrating the removal of air bubbles, in which (a) shows a conventional electrode and (b) shows the electrode according to the present embodiment. [Figure 4] FIG. 2 is a schematic cross-sectional view of a zero-gap type cation exchange membrane process sodium chloride electrolysis cell, taken along a plane passing through a rib of a cathode chamber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] Next, the present invention will be described in detail with reference to the embodiments, but the present invention is not limited to these descriptions. Various modifications of the embodiments may be made as long as the effects of the present invention are achieved.
[0037] As shown in FIG. 4, the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to this embodiment includes a cation exchange membrane 12 serving as a diaphragm, an anode 10 in close contact with one surface of the cation exchange membrane 12, an anode chamber 14 in which the anode 10 is accommodated and filled with anolyte, a cathode 11 in close contact with the other surface of the cation exchange membrane 12, and a cathode chamber 13 in which the cathode 11 is accommodated and filled with catholyte. In this zero-gap type cation exchange membrane process sodium chloride electrolysis cell 100, anode gas is generated in the anode 10 and hydrogen is generated in the cathode 11. The anode 10 includes an electrode substrate made of a perforated plate and an anode coating layer of a hydrophilic electrode active material formed on the surface of the electrode substrate. The electrode substrate is a roll-pressed expanded metal substrate having a perforated plate thickness of t mm, a long-side opening period of LW mm, a short-side opening period of SW mm, and a strand of W mm. the opening ratio of the expanded metal is 20% or more and 60% or less, the ratio calculated by LW / SW is 1.5 or more and 3.5 or less, the plate thickness t of the porous plate is 0.5 mm or more and 1.0 mm or less, the opening period SW of the short side is 2.0 mm or more and 5.5 mm or less, the apparent thickness Pmm of the roll-pressed product is 1.1t or more and 2.0t or less, the cathode 11 has a nickel mesh obtained by plain weaving nickel wires having a wire diameter of 0.06 to 0.16 mm, and a cathode coating layer of a hydrophilic electrode active material formed on the surface of the nickel mesh, the pitch of the cathode 11 being 1 / 2 or less of the SW of the anode 10, and the zero-gap type cation exchange membrane process saline electrolysis cell 100 has an elastic body 15 that applies pressure to the surface of the cathode 11 opposite to the surface in close contact with the cation exchange membrane 12.
[0038] Here, the anode is made of a roll-pressed expanded metal as the anode substrate, which is coated with an electrode active material to form the anode, and the cathode is made of a plain weave mesh made by knitting nickel wires of a specific size relative to the anode substrate, with the cathode having the electrode active material coated on its surface, sandwiched between the cation exchange membrane in the middle, and a force is applied to the cathode surface by an elastic body 15 such as a mat-like spring body made of thin nickel wires, pressing the cathode against the cation exchange membrane from the cathode side, thereby integrating the cathode, cation exchange membrane, and anode, thereby successfully homogenizing the current density in the cation exchange membrane, minimizing the electrical resistance, and obtaining the minimum electrolysis voltage.
[0039] The cathode 11 must be constantly pressed against the cation exchange membrane 12 and in close contact with it. To this end, the cathode 11 is fixed to the rib 17 via the elastic body 15 having a spring function so that the cathode 11 is constantly in close contact with the surface of the cation exchange membrane, and placed on the surface of the cathode current collector 16, which has high physical strength and is porous. The elastic body 15 is a sponge-like mattress made by randomly folding and bundling fine nickel wires or a metal scrubber made of nickel wires, and the cathode current collector 16 is an expanded metal or punched metal made of nickel. Electricity is passed through the cathode current collector 16 and the elastic body 15 to the cathode. The rib 17 is disposed in the cathode chamber 13 and is attached to the electrolytic cell. It is preferable to provide the rib 17 with a liquid passage hole 19 so as not to impede the circulation of the cathode liquid filled in the cathode chamber 13.
[0040] In other words, in conventional cation exchange membrane electrolytic cells, the optimum anode and the optimum cathode are closely attached to each other with the cation exchange membrane sandwiched therebetween, with the main aim of minimizing the electrical resistance caused by the electrolyte containing bubbles generated from the anode and the cathode, and the electrical resistance and the electrolysis voltage are minimized. However, the cation exchange membrane is hardly taken into consideration in this study. However, although the cation exchange membrane is an extremely thin membrane, its electrical resistance is large, and minimizing the electrical resistance is an important factor in reducing the electrolysis voltage. To achieve this, since the cation exchange membrane itself cannot be changed, it is important to make the distribution of the current flowing through the cation exchange membrane as uniform as possible in order to minimize the voltage.
[0041] To make the current density in the cation exchange membrane uniform, it is desirable to make both the anode and the cathode into plates, but in reality, as electrolysis progresses on both the cathode and the anode, bubbles are generated, and electrolyte must be supplied to these areas. Electrolysis generates bubbles, and it is necessary that the generated bubbles escape (are removed) from the electrode part of the electrical resistor and electrolyte is supplied at the same time.
[0042] For this purpose, the electrode shape must be adapted to the characteristics of the bubbles that are generated, and this is also related to the surface characteristics of the cation exchange membrane. In other words, the cation exchange membrane used in salt electrolysis may come into contact with chlorine gas, which is highly oxidizing, and for this reason, a highly corrosion-resistant fluororesin-based cation exchange membrane is used. However, fluororesin is highly water-repellent, so the bubbles generated in the electrolysis reaction are difficult to separate, or the bubbles, which are insulating, may grow large and increase the electrical resistance, which may increase the electrolysis voltage.
[0043] In the cation exchange membrane method of salt electrolysis, the specific gravity of the sodium hydroxide (usually about 32%) generated in the cathode chamber is greater than that of the anolyte (salt solution) (about 200 g / liter), so the cation exchange membrane adheres closely to the anode due to the difference in specific gravity. Naturally, the chlorine gas generated on the surface of the anode by electrolysis grows while adhering to the cation exchange membrane to which it is attached, but on a water-repellent surface, the bubbles of chlorine gas generated do not separate until they grow large. Naturally, the bubbles are insulators, so the electrolysis voltage becomes extremely high. To avoid this, the surface of the cation exchange membrane has recently been specially treated to be highly hydrophilic.
[0044] On the other hand, the anode that is in close contact with the cation exchange membrane may become water-repellent depending on the electrode active material and manufacturing conditions, and the growth of bubbles on the anode surface may increase the electrical resistance and the electrolysis voltage. In addition, when the bubbles grow in this way, there is a problem that it becomes difficult for the gas generated at the contact surface between the cation exchange membrane and the anode to escape to the back side of the electrode.
[0045] On the other hand, the porous body on the anode surface is used in close contact with the cation exchange membrane, which has a very high electrical resistance, and in order to make the current distribution in the cation exchange membrane uniform, it is desirable for the porous body of the anode to be as fine as possible and uniform over the entire surface, and it is natural that large holes cannot be provided in this case to allow air bubbles to escape, and therefore, since it is necessary to remove the air bubbles before they grow, it is essential to maintain the anode surface, that is, the electrode coating, as hydrophilic. Naturally, in addition to this, it is necessary for the anode to have as many repeated fine holes as possible, and also to allow the air bubbles to escape upwards quickly because they are light.
[0046] For this reason, it is necessary to make the current distribution on the anode side as uniform as possible on the cation exchange membrane surface. On the other hand, the chlorine gas bubbles generated by electrolysis are much larger than the hydrogen gas bubbles generated from the cathode, so the structure of the anode must be adapted to this in order to quickly extract the chlorine gas generated from the anode that is in close contact with the cation exchange membrane to the rear.
[0047] In the case of chloralkali electrolysis, the electrode active material of the anode is iridium and ruthenium, and the anode is an oxide containing a stabilizing material.
[0048] The same expanded mesh, plain woven mesh, or perforated plate is also used for the cathode, but what must be considered here is that the anode and cathode must be combined in such a way as to make the current density as uniform as possible within the surface of the cation exchange membrane, which has a high electrical resistance.
[0049] However, the problem is that industrial electrolytic cells are usually large, measuring 1.2m x 2.4m, and it is impossible to control the positional relationship of the anode and cathode relative to the cation exchange membrane surface. For example, if the positional relationship of the cathodes made of the same expanded metal could be fixed while maintaining a certain relationship, it would be possible to give an almost ideal positional relationship, but in reality, it is virtually impossible to control the positional relationship on the order of millimeters in an electrolytic cell on the order of meters. The only possibility seems to be to rotate expanded metals with the same mesh size or an integer multiple or an integer fraction of that size by 90 degrees with respect to each other, which would allow one to approach the ideal positional relationship.
[0050] However, while this may be possible if the expanded metal has a relatively large mesh and is thick, in the case of fine mesh, there is a limit to the size of the original titanium and nickel plates used to make the expanded metal, making it very difficult to freely rotate it by 90 degrees, and there is also the problem that it is difficult to make the mesh of the expanded metal fine.
[0051] Because of its electrical conductivity, the anode side titanium can be made fine by either making it into a punched plate or expanding metal. However, taking into consideration economic efficiency and manufacturing methods, it was found that the most effective electrode is one in which a titanium plate of a certain thickness is made into fine expanding metal, and then roll-pressed to create a fine mesh, with the expanding metal having a slightly tilted electrode mesh as the base material so that the generated bubbles can be more effectively and quickly removed to the rear, and this is coated with a hydrophilic electrode active material so that the bubbles generated by electrolysis are separated from the base material before they grow too large.
[0052] On the other hand, as for the cathode to be combined with this, when the anode is made of expanded metal as mentioned above, there is a high possibility that the current will be biased in the cation exchange membrane due to the similarity of shape of the nickel expanded metal. Therefore, a woven mesh made of nickel base material, easy to adjust in size, and with a completely different shape is required, and it was found that the mesh size is most preferably less than half that of the anode expanded metal. In other words, it was found that the metal-metal distance between the anode and cathode is almost the same in all parts. In other words, it was found that this makes the current density flowing in the cation exchange membrane uniform in almost all parts, and therefore the voltage consumed by the cation exchange membrane is minimized. In addition, when expanding metal is combined with a fine plain weave mesh, the mesh openings sandwiching the anode / cathode cation exchange membrane do not coincide in positional relationship, but are almost uniform regardless of the positional relationship, and it was found that by making the pitch size of the plain weave mesh 1 / 2 or less of the expanded metal openings (specifically, SW), no change in voltage is observed even if the relative positions are changed, and that this change is minimized. As a result, although the current distribution in the cation exchange membrane is not ideal, it becomes uniform within a practical range, and it is found that the resistance loss when the cation exchange membrane is sandwiched between the cathode and anode in a zero-gap type is minimized and uniform.
[0053] Here, the pitch is the value obtained by dividing 1 inch (25.4 mm) by the number of meshes, in other words, the distance between the central axis of a nickel wire and the central axis of an adjacent nickel wire, or the sum of the wire diameter of the nickel wire and the width of the space surrounded by the nickel wire and the adjacent nickel wire.
[0054] That is, the cathode is a nickel porous body with small mesh, that is, a nickel mesh made by plain weaving nickel wires with a wire diameter of 0.06 to 0.16 mm, preferably a nickel wire with a wire diameter of 0.08 to 0.14 mm, and a mesh with a pitch of 1 / 2 or less, preferably 2 / 5 or less, of the anode SW is used as a base material, and a hydrophilic electrode active material similar to the anode is provided on the surface. For example, when the SW is 2 mm and the pitch of the plain weave mesh is 30 mesh, it is 2 / 5. And the lower limit of the pitch of the nickel mesh relative to the anode SW is, for example, 1 / 3. For example, when the SW is 2 mm and the pitch of the plain weave mesh is 40 mesh, it is 1 / 3. As a result, it was found that even if the relative positions of the anode and cathode are arbitrarily given with the cation exchange membrane sandwiched between them, the electrical resistance in the state in which the cation exchange membrane is sandwiched between the cathode and anode in a zero gap type by electrolysis hardly changes and is at a minimum.
[0055] In this embodiment, the pitch of the nickel mesh is preferably 0.6 to 1.2 mm. If the pitch is less than 0.6 mm, depending on the current density, the mesh openings are not sufficiently secured and the air bubbles are concentrated in the mesh openings, resulting in a shortage of the effective cathode area, which may cause the voltage to increase and the current resistance to increase. Alternatively, if the nickel wire diameter is increased, the current resistance will decrease, but the mesh thickness will increase, resulting in a decrease in the effective electrode area. On the other hand, if the pitch exceeds 1.2 mm, the cathode itself has large mesh openings, which may cause the cathode itself to create a current density distribution in the cation exchange membrane.
[0056] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, the electrode active material of the cathode coating layer preferably contains a platinum group metal and / or a platinum group metal oxide, which reduces the overvoltage of the electrode by 300 mV or more compared to the case without the cathode coating layer, i.e., reduces the electrolysis voltage by 300 mV or more, and also improves the wettability of the electrode surface, so that generated bubbles quickly leave the electrode surface, thereby enabling a stable maintenance of a lower electrolysis voltage.
[0057] In the zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to the present invention, the electrode active material of the cathode coating layer preferably contains a composite oxide of ruthenium and cerium, which is not only hydrophilic but also the most active of platinum group metals and platinum group metal oxides, and can maintain its activity and stability for a long period of time.
[0058] In this embodiment, an anode, which is an expanded metal that meets certain conditions, is attached to the surface of the cation exchange membrane. Then, electrolysis occurs at the attached portion, generating chlorine gas on the hydrophilic electrode surface. Then, the bubbles separate before the chlorine gas develops significantly. The chlorine gas passes through the electrode surface that is slightly open outward of the expanded metal, and immediately escapes to the side of the electrode surface opposite the cation exchange membrane. This allows electrolysis with minimal resistance in the electrolyte.
[0059] On the other hand, the hydrogen gas generated at the cathode has bubbles of 10 microns or less in size, and simply diffuses in the electrolyte. Unless there is a large liquid flow in the electrolyte, the cathode will be surrounded by bubbles, and due to the electrical resistance, in the case of a zero gap, if the thickness of the expanded metal is 0.5 mm or more, the effective surface area may constantly change, making the system unstable. The reason for this is unclear, but it is known that during electrolysis, sodium ions from the anode side usually flow to the cathode side along with the entrained water in a cation exchange membrane, and the stable liquid flow caused by this creates a fast liquid flow in the thin part of less than 0.5 mm. This is thought to be because the bubbles are removed and electrolysis is stable. However, if the expanded metal is thick in this range, the back side of the expanded metal cannot be used effectively, making it unstable. Therefore, it is essential to use a flat weave mesh with an extremely thin thickness, and this is also suitable for this case.
[0060] Problems with using an expanded metal cathode include the anode / cathode mentioned above, but on the other hand, the hydrogen gas bubbles generated at the cathode are 10 microns or less in size, so they hardly move unless there is a flow of electrolyte, and an elastic body must be added to press the cathode mesh against the cation exchange membrane, which interferes with the liquid flow and disturbs it. For this reason, the flow of the cathode liquid is mostly due to migration water passing through the cation exchange membrane, and it is believed that hydrogen bubbles can be removed by a fast flow of liquid, and that the current flows effectively only about 0.2 to 0.3 mm from the surface of the cation exchange membrane. Therefore, a plain weave knitted mesh that works sufficiently effectively is effective, and the wire diameter of the mesh must be 0.16 mm or less, and the knitted mesh must be made of thick wires of 0.06 mm or more in order to effectively obtain a large surface area.
[0061] As mentioned above, in terms of the current distribution in the cation exchange membrane, the fine knitted mesh has a shape completely different from that of the anode side expanded metal, and has smaller mesh than the anode expanded metal. The fine plain weave knitted mesh base material of a different shape is also extremely effective in making the current distribution in the cation exchange membrane almost uniform over the entire membrane surface. In order to make the current density in the cation exchange membrane uniform, such a knitted mesh needs to have meshes that are sufficiently smaller than those of the anode mesh, and the pitch of the knitted mesh needs to be 1 / 2 or less the size of the anode SW, as mentioned above. The surface of such a knitted mesh needs to be more hydrophilic and coated with an electrode active material that has a catalytic function to minimize hydrogen overvoltage.
[0062] For example, if the SW of the anode is 2 mm, the line spacing of the plain weave mesh of the cathode must be 1 mm or less, that is, 25.4 mesh or more. In the case of the above 25.4 mesh, which is considered with a wire diameter of 0.1 mm, the repeat area is 1 mm 2 The surface area of the nickel wire in the wire is 2 x 0.1 x π = 0.2π, which is almost the same surface area as the surface of the expanded metal, but is finer and has better uniformity within the surface. It was found that such a combination would produce the best results.
[0063] [anode] The anode is described in more detail below. The anode is an electrode for cation exchange membrane chloralkali electrolysis having an electrode substrate made of a pure titanium perforated plate and a hydrophilic electrode active material coating layer formed on the surface of the electrode substrate, the electrode substrate being a roll-pressed product of an expanded metal having a plate thickness of t mm, a long side opening period of LW mm, a short side opening period of SW mm, and a strand of W mm, the open area ratio of the expanded metal being 20% or more and 60% or less, the ratio calculated by LW / SW being 1.5 or more and 3.5 or less, the plate thickness t of the perforated plate being 0.5 mm or more and 1.0 mm or less, the short side opening period SW being 2.0 mm or more and 5.5 mm or less, and the apparent thickness P mm of the roll-pressed product being 1.1t or more and 2t or less.
[0064] In chloralkali electrolysis using the cation exchange membrane method, the main reaction at the anode is the chlorine evolution reaction. As for the chlorine gas generated by electrolysis, the bubbles themselves become electrically resistant because they are not conductive. Therefore, it is necessary to consider how quickly the bubbles can be removed from the periphery of the anode. In this way, the periphery of the electrode must always be filled with liquid, which is a requirement for stable continuation of electrolysis at a low electrolysis voltage.
[0065] In this embodiment, it is preferable to use an expanded metal made of pure titanium as the base material of the electrode, and the expanded metal has the characteristics that it is relatively easy to manufacture a perforated plate for the electrode, and that, although it is a perforated plate, it has a high titanium utilization rate of 100% compared to other base materials such as punched plates, and is relatively inexpensive. Here, it is preferable that the pure titanium is JIS Class 1 or JIS Class 2 titanium.
[0066] The thickness of the base plate, that is, the plate thickness t of the perforated plate, is 0.5 mm to 1.0 mm. If the plate thickness is smaller than 0.5 mm, the cross-sectional area of the perforated portion of the electrode surface area effective for electrolysis is reduced, so that the actual surface area of the electrode as a whole is reduced, and as a result, the actual current density increases, and as a result, the electrode overvoltage increases slightly, and the life of the electrode may be shortened. Furthermore, the physical strength may be insufficient. On the other hand, if the thickness of the base plate is larger than 1.0 mm, the weight of titanium increases, making it expensive, and it becomes difficult to make the mesh size small. In addition, the current concentrates on the front side of the electrode, that is, the cation exchange membrane side, and the back side cannot be used effectively, so that the effective actual surface area may be reduced. For these reasons, the thickness t of the electrode substrate base plate is 0.5 mm to 1.0 mm, preferably 0.6 mm to 0.9 mm, and more preferably 0.7 mm to 0.8 mm.
[0067] When the expanded metal is made, the external shape of the expanded metal expands by the number of holes to be made, but the ratio of expansion of the plate is its opening ratio. In other words, if the length of the original plate is 1000 mm, the expanded metal made from it will have a If the length of the barrel is 2000 mm, the aperture ratio is (2000-1000) / 2000=0.5, or 50%. If the aperture ratio is 30%, and the length of the perforated plate is x, then x can be expressed by the formula 1. (Number 1)x=0.3x+1000 From (Equation 1), we can find that x is approximately 1429 (mm).
[0068] The mesh size of this expanded metal is defined as the repeating period in the stretched direction, SW, and the repeating period in the perpendicular direction, LW. In other words, a small mesh is one in which LW and SW are small, and the expanded metal has a large number of repeating periods per unit size. Also, as the ratio of LW to SW, LW / SW, increases, the opening of the holes in the porous part becomes elongated, and as LW / SW becomes smaller, that is, closer to 1, the holes become closer to a square.
[0069] For such meshes, it is desirable for the current distribution in the cation exchange membrane, which has a relatively high electrical resistance, to be uniform, and to achieve this, it is better for the expanded metal to have small meshes. However, in reality, air bubbles generated by electrolysis need to be expelled through the openings, i.e. the meshes of the expanded metal, and for this to happen, a certain degree of pore size is essential. Furthermore, even if there are openings, it is difficult for the air bubbles to escape through narrow gaps, such as thin openings. After extensive research into this issue, it was found that it would be sufficient to bring the relationship between the opening rate and the size of the holes in the expanded metal within a certain range.
[0070] Specific examples of preferred mesh shapes for expanded metal are shown in Figure 2. Figure 2(a) shows a diamond shape, and (b) shows a tortoise shell shape.
[0071] The aperture ratio of the expanded metal used here is 20% to 60%, preferably 22% to 55%, more preferably 25% to 50%, and even more preferably 35% to 40%. If the aperture ratio is less than 20%, the titanium area per surface, i.e., the electrode area, will increase, but instead the gaps in the expanded metal will become smaller, which will cause a problem that it will be difficult for the generated bubbles to escape to the opposite side of the cation exchange membrane, i.e., to the back side of the electrode. Therefore, when making the expanded metal, it is desirable to make it three-dimensional even slightly to increase the gaps. It is desirable to make the apparent thickness thicker than the original plate thickness. This will make the actual electrode area larger and make it possible to more effectively allow bubbles to escape to the opposite side of the cation exchange membrane. On the other hand, if the aperture ratio exceeds 60%, the effective area as an electrode will become smaller, which will cause a problem of increased voltage. The extension ratio of the expanded metal used during production is 1.25 to 2.50 times the length of the original sheet, preferably 1.28 to 2.22 times, more preferably 1.33 to 2.00 times, and even more preferably 1.54 to 1.67 times.
[0072] That is, in a normal expanded metal, a plate is expanded to form a porous body, and then roll pressed to the thickness of the original plate to form a porous body with a smooth surface. In contrast, in this embodiment, roll pressing is performed as follows. That is, the original plate (thickness t mm) is expanded to form a porous body. The apparent thickness of the porous body before roll pressing at this time is T mm. Then, the porous body is roll pressed to press it to a thickness 1.1 to 2.0 times that of the original plate. That is, the apparent thickness P mm of the roll pressed product is set to 1.1t or more and 2t or less. The roll pressed product is not pressed to the thickness of the original plate, so it can be said to be a weakly pressed product.
[0073] Here, we will consider an example of a porous body made by expanding metal processing a plate. Figure 1 shows a schematic diagram of a porous body made by expanding metal processing. As shown in Figure 1, the thickness of the plate before expanding metal processing and the thickness of the porous body are the same, and are denoted as t (mm). The opening period of the long side of the porous body is denoted as LW (mm), the opening period of the short side is denoted as SW (mm), and the strand is denoted as W (mm). The apparent thickness of the expanded metal before roll press is denoted as T (mm). In this case, T is expressed by (Equation 2). (Equation 2) T = 2W / SW·{t + √(SW 2 -4W 2 )}
[0074] As shown in Figure 1(b), the manufacturing conditions of expanded metal usually result in an apparent thickness T that is expressed by the formula 2, which is determined by the original plate thickness (t) and the plate feed width (strand (W)) during the manufacturing of the expanded metal, and if the expanded metal is considered as a flat plate, the metal part is inclined relative to it, and is considerably thicker than the original plate. When it is made into expanded metal, the opening ratio is given by the strand and the repeating period in the extension direction, SW.
[0075] If the measured apparent thickness of the expanded metal before roll pressing is K, K has the relationship of (Equation 3) with respect to the calculated apparent thickness T of the expanded metal obtained by (Equation 2). (Math 3)K=α·T Here, 0.7≦α≦1.0 α is a correction coefficient. During the actual expanded metal processing, the ends of the metal parts tend to become rounded or distorted, so the actual measured value tends to be slightly smaller than the calculated value.
[0076] The unrolled expanded metal with apparent thickness K is roll-pressed to have an apparent thickness Pmm of 1.1t to 2t. At this time, there is almost no change in LW, SW, W, and t before and after roll pressing.
[0077] For the anode of salt electrolysis using the cation exchange membrane method, an inclined structure is rolled down to the thickness (t) of the original plate to make a simple perforated plate. This makes it easy to handle, but it has little effect especially when the perforations of the perforated plate are relatively large. However, the generated bubbles first flow in the plate thickness direction at right angles to the cation exchange membrane, and then flow along with the liquid flow, which causes a problem of poor bubble removal. This is because when the plate is thin and the aperture ratio is low, the apparent perforations become small, and in the case of chlorine, which has much larger bubbles than hydrogen, the bubble removal condition becomes poor.
[0078] In this embodiment, this is pressed by roll pressing to a thickness 1.1 to 2.0 times that of the original plate. This makes the porous portion tilted, and by utilizing this tilt and tilting it upward from the cation exchange membrane side to the back side of the electrode, it becomes possible to remove air bubbles without resistance along the flow of the air bubbles.
[0079] Figure 3 shows an explanatory diagram of the escape of air bubbles. When the expanded metal is smoothed to the same thickness as the original plate as in the case of normal cation exchange membrane electrolysis, the contact surface between the expanded metal and the cation exchange membrane is maximized, and it is thought that electrolysis can be performed most efficiently. However, in reality, the air bubbles generated by electrolysis move to the opposite side of the cation exchange membrane, that is, to the back side of the electrode, and then flow upward. However, they are blocked by the cross section of the electrode, and once they come out horizontally, they have to rise by the buoyancy of the air bubbles themselves. This resistance prevents the air bubbles from escaping, and the amount of air bubbles in the liquid increases, albeit slightly, as the rising speed slows down (see Figure 3(a)). In other words, there is a problem that the electrical resistance of the electrolyte increases substantially.
[0080] In this embodiment, these factors are taken into consideration, and the cation exchange membrane actually swells slightly during use, and even if the anode has slight unevenness due to the pressure of the catholyte, it follows the unevenness and adheres to the anode. The unevenness that allows this is preferably 1.2 to 2.0 times the thickness of the pure titanium plate before processing, and more preferably 1.2 to 1.5 times. This allows the generated bubbles to rise diagonally upward on the opposite side to the cation exchange membrane, with minimal resistance, without moving horizontally (see FIG. 3(b)). Depending on the degree of swelling of the cation exchange membrane, the degree of smoothing of the electrode may be slightly changed to 1.4 to 2.0 times, and it is desirable to select an appropriate amount depending on the cation exchange membrane.
[0081] The LW / SW, which is related to the size and shape of the mesh of the expanded metal, is 1.5 to 3.5, preferably 1.6 to 2.5, and more preferably 1.7 to 2.0. The LW / SW shown here is related to the aspect ratio of the opening of the expanded metal, the diamond shape, and as the LW / SW increases, the long diameter of the diamond becomes larger relative to the short diameter, so that even if the opening area is the same, the mesh becomes narrower and it becomes difficult for the bubbles to escape. Therefore, it is desirable for the opening to be close to a diamond with an aspect ratio close to 1:1. To achieve this, it is desirable for the LW / SW ratio to be close to 1, but from the perspective of the workability of titanium, it is thought that the limit is about 1.5, and if it is smaller than that, processing becomes difficult. If the LW / SW is larger than 3.5, depending on the size of the mesh, there is a high possibility that a thin part will be formed in the diamond part of the opening, and the escape of the bubbles will not be complete.
[0082] In this embodiment, the opening period SW of the short side is 2.0 mm or more and 5.5 mm or less, preferably 2.0 mm or more and 5.0 mm or less, and more preferably 2.2 mm or more and 4.5 mm or less. The size of SW is determined by the strand (W) and opening rate of the expanded metal, but in the case of cation exchange membrane method salt electrolysis, in the production of expanded metal, it is determined to be as small as possible within the range where generated bubbles can easily escape. Furthermore, in order to stably produce expanded metal, the plate thickness (t) and strand (W) are sometimes made to be approximately the same size. The SW of the expanded metal is determined by these factors.
[0083] Next, a method for producing an anode according to this embodiment will be described. The method for producing an electrode for chloralkali electrolysis using a cation exchange membrane method includes the following steps.
[0084] (Process 1) An expanded metal is prepared, the perforated plate being made of pure titanium and having a thickness of t mm, a long side opening period of LW mm, a short side opening period of SW mm, strands of W mm, and an apparent thickness of K mm. (Process 2) The expanded metal is roll-pressed to produce an electrode substrate having an apparent thickness of P mm. (Step 3) A hydrophilic electrode active material coating layer is formed on the surface of the roll-pressed product.
[0085] In the roll-pressed product, the opening rate of the expanded metal is 20% or more and 60% or less, the ratio calculated by LW / SW is 1.5 or more and 3.5 or less, the plate thickness t of the perforated plate is 0.5 mm or more and 1.0 mm or less, the opening period SW of the short side is 2.0 mm or more and 5.5 mm or less, and the apparent thickness Pmm of the roll-pressed product is 1.1t or more and 2t or less.
[0086] So far, the shape of the electrode substrate of the anode has been described, but the size of the chlorine gas bubbles generated from the anode is usually 100 times larger than the size of the hydrogen bubbles generated from the cathode, and it varies depending on the hydrophilicity of the electrode surface, the hydrophilicity of the cation exchange membrane, and even the unevenness of the electrode surface. The porous parts of the anode expanded metal are relatively small because they are arranged in a large number and fine manner, and although the bubbles are easily removed at an angle in this embodiment, it is desirable for smaller bubbles to pass through the electrode part. To achieve this, a hydrophilic electrode active material coating layer is provided. It is also preferable to process the surface of the electrode substrate.
[0087] The method for producing an anode preferably further includes, between step 2 and step 3, step 4 of subjecting the roll-pressed product obtained in step 2 to a surface blasting treatment, and step 5 of etching the surface-blasted roll-pressed product with high-temperature hydrochloric acid to remove sharp protrusions and sharp edges on the surface.
[0088] (Step 4) For this purpose, it is preferable to make the surface of the expanded metal substrate uneven by blasting, remove burrs, and smooth the corners and edges. Smoothing the corners is particularly important because the porous portion is inclined and may come into contact with the cation exchange membrane at an acute angle, so it is important to avoid damaging the cation exchange membrane at these points. For example, in the case of sandblasting, it is preferable to use white alumina shot, a powder with an average particle size of about 0.5 mm, as the medium and perform the treatment at a pressure of about 0.2 to 0.5 MPa. However, this should be adjusted depending on the thickness of the titanium base plate used. Of course, it is also possible to use media such as SiC powder or zircon sand if the same characteristics can be obtained.
[0089] Furthermore, blasting with iron grit or iron shot can sometimes be used to roughen the surface, but this requires high blast pressure and blasting tends to leave iron in the titanium base material, which in turn requires excessive etching of the base material to remove. Although it is not impossible, this method is not recommended.
[0090] (Step 5) After blasting, it is preferable to etch the surface with a high-temperature hydrochloric acid solution in order to completely remove the blasting powder remaining on the surface, to smooth the sharp irregularities created by blasting, and to activate the surface of the substrate. The reason why hydrochloric acid is used as the etching acid is that it has a strong etching effect and smoothes the sharp irregularities created by blasting, etc., and this improves the separation of bubbles generated during electrolysis, so that the bubbles leave the substrate surface before they grow large, and the bubbles become small and quickly escape from the anode. In addition, countless fine titanium hydrides are generated on the surface of the titanium substrate by hydrochloric acid etching, so that if an electrode coating is applied to the surface, it will have extremely strong adhesion. The conditions for hydrochloric acid etching are a hydrochloric acid concentration of 18% to 25%, and a temperature of 90°C to 107°C (boiling) are preferable. The treatment time is preferably 10 to 15 minutes, and the weight loss of titanium is 30 to 70 g / m 2 - A projection surface is preferable, but is not limited to this.
[0091] A composite oxide-type electrode coating is applied to the surface of the substrate thus prepared. At least the surface of this electrode coating must be hydrophilic. This allows the generated gas (chlorine gas) to separate bubbles well, and therefore the bubbles become finer and easier to remove. The hydrophilic coating used here is preferably formed by a normal pyrolytic coating method. The solvent of the coating liquid is preferably a liquid mainly composed of alcohol. However, the electrode prepared in this way has the problem that the electrode wears out at a relatively high rate. Therefore, in consideration of durability, it is recommended that the base be coated using a normal hydrochloric acid solvent liquid, and then the surface be coated with pyrolytic coating from the liquid that will become the hydrophilic coating described here. In other words, it is possible to laminate two or more types of coatings. Of course, if necessary, only one type of hydrophilic coating may be used.
[0092] More specifically, step 3 preferably includes step 3-1 of applying a coating liquid consisting of a dilute hydrochloric acid solution containing ruthenium or a dilute hydrochloric acid solution containing ruthenium and iridium to the surface of the roll-pressed product, and repeating thermal decomposition multiple times, and step 3-2 of applying a coating liquid containing ruthenium and mainly composed of alcohol as a solvent, or a coating liquid containing ruthenium and iridium and mainly composed of alcohol as a solvent, and performing thermal decomposition coating one or more times to make the surface of the electrode active material coating layer hydrophilic.
[0093] Although the components of the electrode coating are not specified here, it is preferable that the electrode active material coating layer is an oxide coating layer consisting of two components, ruthenium or ruthenium and iridium, as the electrode active material, titanium or tin, or two components of titanium and tin, as a stabilizer, and further containing other components as necessary. These can be used by improving the components that have been used conventionally. However, the electrode coating on the electrode surface must be strongly hydrophilic. In addition, when a long-life electrode is required as in the current situation, it is preferable to use a composite oxide in which ruthenium and iridium are used as the electrode active material and titanium is added as a stabilizer.
[0094] For hydrophilic coating, it is desirable to use an alcohol-based liquid such as n-butanol or iso- or n-propanol as the solvent for the coating liquid containing these electrode active materials, rather than an aqueous solution, and to perform the coating under adjusted coating conditions. This makes it possible to obtain a coating layer with a strong hydrophilic surface. In addition, since the hydrophilic coating produced in this way has the characteristic that the electrode active material is consumed slightly more than when dilute hydrochloric acid is used as the solvent, it is also recommended to apply an aqueous coating to the base layer and then layer a coating using an alcohol-based liquid on the base layer.
[0095] The electrode coating layer made from an aqueous solution system here is initially hydrophobic and has the characteristic of having a slightly high potential; however, after several months to three years of electrolysis, the potential decreases and the electrode becomes hydrophilic. Therefore, by using such an electrode coating of two or more layers for continuous use, it is possible to maintain a low potential and hydrophilicity over a long period of time.
[0096] This reduces the current to 6kA / m 2 to 8kA / m 2 The electrolysis is extremely excellent at a large current density and, together with the low overvoltage, the influence of bubbles generated by electrolysis is minimized, that is, electrolysis at a low electrolysis voltage is possible.
[0097] [Formation of cathode coating layer] When the electrode active material of the cathode coating layer contains platinum group metals and / or platinum group metal oxides, the method of formation is basically the same as that of the anode, and is manufactured by pyrolysis. That is, the surface of the nickel plain weave mesh substrate is roughened by blasting and hydrophilized, and then etching is performed to create fine irregularities on the surface and activate the surface. However, in the case of such a fine mesh, the deformation may become too large when mechanical force such as blasting is applied, so that a treatment by an etching method that roughens the surface is desirable. For example, the surface can be slightly matte-finished and activated by immersing the substrate at room temperature for 3 to 5 minutes in an etching solution obtained by mixing nitric acid, acetic acid, and acetone in a 1:1:1 (molar ratio). The concentration of the etching solution at this time can be diluted with deionized water to obtain the desired state. After the surface is roughened and activated in this way, a coating solution containing an electrode catalyst material is applied. It is preferable to apply the coating by spraying, but it can also be applied by a brush or rubber roller. In the case of plain weave, the applied coating liquid tends to accumulate at the intersections between the nickel wires, but with proper etching, the liquid spreads due to the capillary effect that exists in large numbers on the nickel surface, and a coating layer of almost uniform thickness can be created on the nickel surface. This is then dried and heated and pyrolyzed at a specified temperature to form an electrode coating containing platinum group metals and / or platinum group metal oxides. By repeating the process from application to pyrolysis, a coating layer of the required thickness can be formed. However, compared to the anode coating liquid, the cathode coating liquid requires a solvent with a lower viscosity to dissolve the coating material, so that the liquid's wettability and viscosity can be improved and the viscosity can be reduced. For example, n-butanol is usually used for the anode, but for the cathode, it is necessary to use iso- or n-propanol, which have lower viscosity.
[0098] When the electrode active material of the cathode coating layer contains a composite oxide of ruthenium and cerium, the cathode substrate is degreased with a neutral detergent, and then immersed in an etching solution obtained by mixing nitric acid, acetic acid, and acetone in a molar ratio of 1:1:1 until the metallic luster of the surface changes slightly. Then, cerium chloride is mixed into the ruthenium chloride hydrochloric acid solution so that the metal molar ratio is 2:1, and the solution is diluted with a 10% HCl solution:n-propanol = 1:1 solution by volume. The nickel substrate is immersed in this solution as a coating solution for 1 minute, and then it is roughly dried while blowing cold air from above to blow off excess coating solution. After that, it is dried at 40°C for 10 minutes, and then thermally decomposed at 500°C to form a RuO2-SrO2 composite oxide layer. By repeating this process, a coating layer with a hydrophilic surface and a predetermined coating amount can be formed.
[0099] [Elastic body] The elastic body is preferably a spring-like body, and examples of the spring-like body include a sponge-like mattress made of nickel wire randomly folded and bound, or a metal scrubbing pad made of nickel wire. The elastic body 15 is preferably placed between the cathode current collector 16 and the cathode 11.
[0100] [Anode support] The anode 10 is supported by a support. For example, the anode 10 is directly welded to the frame of the electrolytic cell and to a rib 18 attached to the electrolytic cell. The rib 18 is preferably provided with a liquid passage hole 20 so as not to impede the circulation of the anolyte filled in the anode chamber 14.
[0101] According to this embodiment, in the zero-gap cation exchange membrane chloralkali electrolysis, electrolysis can be performed at an extremely low electrolysis voltage, the chlorine generation efficiency is extremely excellent, and the anode has a long and stable life. That is, by slightly tilting the mesh of the porous portion of the expanded metal slightly upward from the cation exchange membrane side to the opposite side (back side) of the cation exchange membrane, the escape of bubbles is improved. In addition, by improving the electrode surface and making the electrode coating itself hydrophilic, the escape of bubbles is improved, and the bubble diameter is further reduced, and the escape of bubbles from the electrode is improved. As a result, even if the current density is increased and the bubble rate around the electrode is increased, the generated bubbles remain small and escape to the rear at a faster rate. As a result, even if the current density is increased, the increase in voltage is minimized, and the voltage itself can be kept low.
[0102] When an electrode with a longer life is required, a compact electrode coating is applied to the base using a coating liquid of an aqueous solvent, and then a hydrophilic electrode coating of a hydrophilic alcohol solvent is layered on the surface. This makes it possible to keep the cell voltage low from the beginning and to perform stable electrolysis over a long period of time. EXAMPLES
[0103] <Test 1> As an anode, an expanded metal (with a diamond-shaped mesh) with SW=3.0mm, LW=5.0mm, and an aperture ratio of 40% was prepared from a pure titanium plate with a thickness of t=0.8mm. The strand (W) was approximately 0.9mm, and the apparent thickness of the expanded metal before roll pressing was 1.8 to 1.9mm. The expanded metal was roll pressed to prepare porous titanium bodies with apparent thicknesses P (also written as electrode thickness P in the table) changed as in tests 1-1 to 1-7, and these were blasted at a pressure of 0.2MPa using white alumina sand as a medium. Furthermore, etching was performed for 10 minutes in a 20% hydrochloric acid solution at 95°C to clean and activate the surface. The surface of the porous titanium body thus prepared was coated with an electrode active material. That is, the coating liquid was prepared by dissolving iridium chloride, ruthenium chloride, and titanium butoxide in n-butyl alcohol. The composition of the metal components in the coating liquid was iridium:ruthenium:titanium=16.7:33.3:50.0 in terms of metal molar ratio. This coating liquid was applied with a brush to the surface of the blasted and etched titanium porous body, dried at 60°C, and then thermally decomposed for 10 minutes at 510°C. The application, drying, and thermal decomposition operations were repeated 10 times, resulting in a hydrophilic anode coating layer of electrode active material with a total amount of iridium and ruthenium of 8 g / m per projected surface of the titanium porous body. 2 A composite oxide coating equivalent to that of the cathode was formed. Next, pure nickel wire with a diameter of 0.12 mm was woven to prepare a plain weave mesh of 25 meshes as the cathode. The pitch of this mesh was 1.02 mm both vertically and horizontally. The pitch / SW was 0.34. This mesh was blasted with white alumina sand at a pressure of 0.15 MPa, and then the surface was etched and activated with a 20% hydrochloric acid solution at 60°C. The etched and activated mesh was then coated with a coating solution prepared by dissolving dinitrodiammine platinum and cerium chloride in a 1:1 mixture of n-propanol and pure water, and pyrolyzed at 450°C. The coating / pyrolyzation process was repeated eight times to obtain a coating of platinum at 5 g / m2. 2The anode and cathode thus prepared were placed in an experimental zero-gap type cation exchange membrane electrolytic cell, and the electrolysis voltage was measured. The operating temperature was 85°C, and the current density was 0.6 A / cm. 2 After performing preliminary electrolysis for 10 hours at 100°C, the electrolysis voltage was measured. The anolyte was 200g-NaCl / L, but the pH was not adjusted. As shown in Table 1, the electrolysis voltages of Tests 1-2 to 1-6 were lower than that of the conventional expanded metal electrode (Test 1-1) in which the thickness of the base material was obtained by pressing, and were found to be 2.95V or less. The electrolysis voltage of Test 1-7 exceeded 2.95V. This is because the thickness of the electrode was large due to insufficient pressing, and the electrolysis current was concentrated more on the front side of the electrode. Here, in order to change the positional relationship between the cathode and the anode, the cathode was rotated by 90° in the plane and the voltage was measured, but there was no change at all, and it was found that the change in the current density in the cation exchange membrane could be ignored.
[0104] [Table 1]
[0105] <Test 2> As an anode, an expanded metal was prepared with a thickness of t=0.6 mm, LW=4.0 mm, SW=2.5 mm, and the aperture ratio changed as in Tests 2-1 to 2-7. The apparent thickness before roll pressing was 1.7 mm with an aperture ratio of 10% in Test 2-1, and 1.0 mm with an aperture ratio of 70% in Test 2-7. The thickness P of these expanded metals was set to 0.9 mm by roll pressing. This was equivalent to 1.5 times the original plate thickness. After pretreatment was performed using the titanium porous body obtained as an electrode substrate, an anode coating layer of a hydrophilic electrode active material was provided, and the characteristics were measured as an anode. The prepared titanium porous electrode substrate was blasted at a pressure of 0.2 MPa using SiC powder as a medium, to provide unevenness on the surface and to homogenize the surface state. Thereafter, etching was performed for 10 minutes with a 20% hydrochloric acid aqueous solution at 90°C. The same coating solution as in Test 1 was used for this, and coating was performed under the same conditions to prepare an anode. The same activated cathode as in Test 1, in which a hydrophilic electrode active material cathode coating layer was provided on the surface of a nickel plain weave mesh, was used as the cathode. The pitch / SW was 0.41. The same experimental zero-gap cation exchange membrane electrolytic cell as in Test 1 was used for these, and electrolysis was performed under the same conditions to measure the potential and electrolysis voltage. The results are shown in Table 2. In the case of Test 2-1, where the aperture ratio was 10%, the effective electrode area was certainly large, but the aperture was very small, and therefore air bubbles accumulated between the electrode and the cation exchange membrane, making it difficult to pass electricity at a large current density. The electrolysis voltage was far above 2.95 V. In Test 2-7, it was observed that the electrolysis voltage increased (to 3.20 V) because the effective area of the electrode itself became smaller as the aperture ratio increased. In addition, the position of the cathode was changed on the surface of the cation exchange membrane in the same manner as in Test 1, but no change in the electrolysis voltage was observed for each anode.
[0106] [Table 2]
[0107] <Comparative test> The titanium porous body of Test 2 was processed in the same manner as Tests "Pair-1" to "Pair-7" except that the expanded metal was pressed to the same thickness as the original plate, 0.6 mm, and the surface treatment and coating were also the same to prepare anodes. Electrolysis was performed on these under the same conditions as Test 2, and the electrolysis voltage was measured. The results are shown in Table 3. The pitch / SW was 0.41.
[0108] [Table 3]
[0109] As shown in Table 3, the electrolysis voltage in all cases was significantly higher than 2.95 V. This resulted in increased power consumption.
[0110] <Test 3> As the anode, a pure titanium plate having a thickness of 1.0 mm was used with an aperture ratio of 50% and a SW of 3.0 mm, and expanded metals with LW=4.0 mm, 6.0 mm, 7.0 mm, 8.0 mm, 10.0 mm, and 12.0 mm were prepared as in Tests 3-1 to 3-7. Among these, for Test 3-1 with LW=4.0 mm, it was found that the manufacturing was possible but that cracks had occurred partially, and that it was not suitable for the purpose. Except for Test 3-1 with LW=4.0 mm, the apparent thickness P was processed to 1.2 mm by roll press processing. These were first subjected to hydrophobic electrode coating under the following conditions, and the surface was subjected to hydrophilic electrode coating to prepare an anode. As a comparative example, one that was subjected to only hydrophobic electrode coating was prepared (Test 3-7). The surfaces of the expanded metals prepared as described above were subjected to blasting at a pressure of 0.25 MPa using white alumina as blasting powder. After that, etching was performed for 10 minutes with a 20% hydrochloric acid solution maintained at 100°C. After preparation in this manner, the following pyrolysis coating was performed. First, two types of coating liquids with the same composition but different raw materials were prepared. In other words, the metal components of the coating were three components of iridium, ruthenium, and titanium, and the composition was iridium:ruthenium:titanium = 30:30:40 (molar ratio) in terms of metal mass ratio in both cases. Coating liquid 1 was prepared by using iridium chloride, ruthenium chloride, and a titanium tetrachloride aqueous solution as raw materials, and dissolving these in a 10% hydrochloric acid aqueous solution. Coating liquid 2 was prepared by using iridium chloride, ruthenium chloride, and orthotitanium butoxide as raw materials, and dissolving these in n-butanol. The coating conditions were 1 g / m of iridium + ruthenium per titanium surface. 2(projection surface), and then dried at 60°C for 10 minutes, then heated and pyrolyzed at 480°C for 10 minutes, and then allowed to cool. This operation was repeated as many times as necessary. That is, first, the operation of coating, drying, and pyrolysis was repeated five times with coating liquid 1, and then the operation of coating, drying, and pyrolysis was repeated five more times with coating liquid 2 on the surface to form an anode. As a comparative example, an anode was prepared by repeating the coating, drying, and pyrolysis 10 times using only coating liquid 1, as test 3-7. As the cathode, a 30-mesh knitted mesh was prepared by plain weaving nickel wire with a wire diameter of 0.1 mm, and blasting and etching were performed in the same manner as in test 1, and then platinum-cerium oxide coating was performed in the same manner to prepare an activated cathode. The pitch of the nickel mesh was 0.85 mm. The pitch / SW was 0.28. Using the anode and cathode prepared by these methods, an electrolytic cell was assembled under the same conditions as in Test 1, and electrolysis was performed under the same conditions as in Test 1. The results are shown in Table 4. As shown in Table 4, when LW / SW was larger than 3.5 times as in Test 3-6, the small mesh area expanded, which led to poor bubble removal and the electrolysis voltage exceeded 2.95 V. In Test 3-7, the electrolysis voltage was higher than in Test 3-5, probably because the hydrophobic coating was used and the bubbles generated by electrolysis were large. The position of the cathode was changed on the surface of the cation exchange membrane as in Test 1, but no change in voltage was observed. In other words, it was found that even if the positional relationship between the anode and cathode through the cation exchange membrane was changed, there was essentially no change in the current density in the cation exchange membrane.
[0111] [Table 4]
[0112] <Test 4> For a pure titanium plate having a thickness of 1.0 mm, an opening ratio of 40% and LW of 6.0 mm were used to manufacture expanded metals with SW of 2.0 mm, 3.0 mm, 4.0 mm, and 5.0 mm as in Tests 4-1 to 4-4. The expanded metals were roll-pressed to an apparent thickness P of 1.2 mm. The roll-pressed expanded metals of titanium with the same apparent thickness P were blasted in the same manner as in Test 1, and further etched in 20% hydrochloric acid held at 90°C to purify and activate the surface, after which a hydrophilic electrode active material was coated on the surface. The anode coating was an oxide system consisting of ruthenium, titanium, and tin. That is, ruthenium chloride, tin dichloride, and titanium tetrachloride aqueous solutions were dissolved in a mixed solution of n-butanol and 10% hydrochloric acid aqueous solution in a volume ratio of 1:1 to prepare a coating solution. The composition of the metal components in the coating solution was ruthenium:tin:titanium=15:15:70 in terms of metal molar ratio. This coating liquid was applied with a brush so as to be spread evenly over the entire surface of the blasted and etched titanium expanded metal, dried at 110°C, and then thermally decomposed in a muffle furnace at 470°C for 10 minutes in circulating air. The application, drying, and thermal decomposition process was repeated 10 times, and then heat treatment was carried out in circulating air at 470°C for 1 hour to form an electrode. As a result, the amount of coating was 1 m2 of projected surface. 2The amount of ruthenium per unit weight was 10 g. The same cathode as that used in Test 3 was used as the cathode. The pitch / SW was 0.43 in Test 4-1, 0.28 in Test 4-2, 0.21 in Test 4-3, and 0.17 in Test 4-4. The potential and electrolysis voltage of the zero-gap type cation exchange membrane electrolytic cell were measured for the electrodes prepared in this way under the same conditions as Test 3. When the bubbles coming out of the electrode by electrolysis were observed, the growth of the bubbles on the electrode surface was very small, and it was confirmed that the electrode had a hydrophilic surface. On the cathode side, the cation exchange membrane surface was visible to some extent, but the back side was covered with almost white bubbles, and it was recognized that the bubbles were almost uniform and had very little movement. The measurement results of the potential and electrolysis voltage for Tests 4-1 to 4-4 are shown in Table 5. As shown in Table 5, the anode potentials of Tests 4-1 to 4-3 are almost the same, including the comparative example of Test 4-4. However, in the comparative example of Test 4-4, the porous portion is large, but the distance between the holes is wide, so the apparent electrolysis voltage is large. However, as described above, the cathode side is the same in all cases, and it was recognized that the state of the generated bubbles at the anode changed. As in Tests 1 to 3, the cathode was rotated on the surface of the cation exchange membrane to change the relative position between the anode and the cathode, but no change in the electrolysis voltage was observed, and no change was observed in the current distribution in the cation exchange membrane. It was also found that the change in the electrolysis voltage corresponded to the change in the anode. In Test 4-4, the strands were large, and the blind area on the surface of the cation exchange membrane was large, so it was thought that the generated bubbles were not easily removed, resulting in a high electrolysis voltage.
[0113] [Table 5]
[0114] <Test 5-I> A pure titanium plate having a thickness of 0.5 mm was used to prepare expanded metal sheets with an aperture ratio of 20%, an LW of 6.0 mm, and SW of 1.8 mm, 2.0 mm, 2.5 mm, 3.0 mm, and 4.0 mm as in Tests 5-1 to 5-5. The expanded metal sheets were roll pressed to an apparent thickness P of 0.9 mm. These titanium expanded metal sheets with the same thickness were pretreated and coated with an electrode active material under the same conditions as in Test 4 to prepare electrodes. The amount of electrode coating was 1 m of projected surface. 2 The amount of ruthenium per unit weight was 8 g. The potential and electrolysis voltage of the zero-gap type cation exchange membrane electrolytic cell were measured for the electrode thus prepared under the same conditions as in Test 4. Here, the cathode was prepared by plain weaving nickel wires with a wire diameter of 0.1 mm to prepare a 30-mesh knitted mesh, as in Test 3, and then blasting and etching were performed in the same manner as in Test 1, followed by coating with platinum-cerium oxide to prepare a cathode having a hydrophilic cathode coating layer of electrode active material. The pitch of this mesh was 0.85 mm. As can be seen here, in Tests 5-1 to 5-5, the pitch of the cathode plain weave nickel mesh was 1.8 mm, 2.0 mm, 2.5 mm, 3.0 mm, and 4.0 mm in the anode SW, respectively, while the pitch / SW was 0.47, 0.43, 0.34, 0.28, and 0.21 in the order, and the ratios calculated by pitch / SW were all smaller than 0.5. Perhaps for this reason, the cathode was rotated on the surface of the cation exchange membrane as in Test 4, and the relative positions of the anode and cathode were changed, but no change was observed in the electrolysis voltage. In other words, when the size relationship between the cathode and anode is as described above, the relative positions of the anode and cathode have almost no effect. The measurement results are shown in Table 6.
[0115] [Table 6]
[0116] <Test 5-II> For a pure titanium plate having a thickness of 0.5 mm, the processing was basically the same as in Test 5-1 except that the aperture ratio was set to 25%, and titanium perforated plates were produced by changing the strands as in Tests 5-6 to 5-9. These were used as electrode substrates and pretreated under exactly the same conditions as in Test 5-1, a hydrophilic electrode active material coating layer was provided, an electrode was produced, and measurements were performed as the electrode under the same conditions as in Test 5-1. The same cathode as in Test 5-1 was used. That is, the pitch of the cathode nickel mesh was 0.85 mm. The pitch / SW was 0.47 in Test 5-6, 0.43 in Test 5-7, 0.34 in Test 5-8, and 0.28 in Test 5-9. The results are shown in Table 7. The cathode was rotated on the surface of the cation exchange membrane in the same manner as in Test 5-1, and the positional relationship between the anode and the cathode was changed, but no change in the electrolysis voltage was observed.
[0117] [Table 7]
[0118] <Test 6> A pure titanium plate with a thickness of 0.8 mm was used as the anode, and an expanded metal with SW=2.2 mm, LW=3.5 mm, and an aperture ratio of 30% was prepared, and the apparent thickness P was adjusted to 1.15 mm by roll pressing. This expanded metal was blasted and pickled under the same conditions as in Test 1, and electrode-coated under the same conditions as in Test 1 to form an anode. A nickel wire with a diameter of 0.12 mm was used as the cathode, and the pitch size was changed to 1.69 mm, 1.27 mm, 1.02 mm, 0.85 mm, 0.74 mm, and 0.64 mm in order as in Tests 8-1 to 8-6, to prepare plain weave meshes equivalent to 15, 20, 25, 30, 35, and 40 meshes. The pitch / SW was 0.77 for Test 8-1, 0.58 for Test 8-2, 0.46 for Test 8-3, 0.39 for Test 8-4, 0.34 for Test 8-5, and 0.29 for Test 8-6. For these, etching was performed with a solution of nitric acid, acetic acid, and acetone in a molar ratio of 1:1:1 as a pretreatment, and then ruthenium chloride and cerium chloride were dissolved in a solution of 10% hydrochloric acid and n-propanol in a volume ratio of 1:1 so that the metal molar ratio was 2:1. The coating was applied by immersion in the liquid, and the excess coating was blown off with a blower, and then thermal decomposition was performed at 550 ° C. This was repeated to produce a composite oxide coating made of ruthenium oxide-cerium oxide. The anode and cathode prepared here or a cation exchange membrane was sandwiched between them, and the electrodes were incorporated into the same electrolytic cell as in Example 1, and electrolysis was performed as a zero-gap type electrolytic cell. As in Tests 1 to 5, the cathode was allowed to rotate on the surface of the cation exchange membrane to observe the change in electrical resistance inside the cation exchange membrane. The results are shown in Table 8. As can be seen, there were no problems with the electrolysis voltage in Tests 8-1 and 8-2, but it was observed that the cell voltage changed slightly when the cathode was rotated. This was thought to be due to the resistance inside the cation exchange membrane changing due to the change in the relative positions of the meshes between the anode and cathode. It was also found that if the pitch of the cathode plain weave mesh was 1 / 2 or less of the anode SW, there would be no change in voltage, meaning that the electrical resistance inside the cation exchange membrane would be kept to a minimum.
[0119] [Table 8]
[0120] <Test 7> A pure titanium plate with a plate thickness of 0.8 mm was used as the anode, and an expanded metal with SW=2.2 mm, LW=3.5 mm, and an aperture ratio of 30% was produced. The produced expanded metal was roll-pressed to an apparent thickness P of 1.2 mm. An electrode coating was produced for this substrate under the same conditions as in Example 1 from pretreatment to coating. This resulted in an anode with a hydrophilic surface. For the cathodes in Tests 9-1 to 9-7, seven types of nickel wires with diameters of 0.05 mm, 0.06 mm, 0.08 mm, 0.10 mm, 0.14 mm, 0.16 mm, and 0.18 mm were used in order, and a plain weave mesh was produced for each. The size of the plain weave was 25 meshes, and the pitch was 1.02 mm. The pitch / SW was 0.46. These plain woven nickel meshes were used as electrode substrates, and the surfaces were subjected to surface blasting treatment at a pressure of 0.3 MPa using SiC powder as blasting powder, and then etched for 10 minutes with 20% hydrochloric acid heated to 60°C. Furthermore, a solution in which dinitrodiammine platinum was dissolved in isopropanolamine and pure water was diluted with a solution in which iso-propanol and H2O were mixed at a volume ratio of 1:1 to form a coating solution, which was applied to the surface of the electrode substrate, dried, and then pyrolyzed at 450°C for 10 minutes. This application and pyrolysis process was repeated six times to form a cathode coating layer of the electrode active material. When water droplets were dropped on the surface of this cathode, the water spread on the mesh surface, confirming that it was hydrophilic. The cathode was attached to the zero-gap type cation exchange membrane discharge tank used in Test 6, and electrolysis was performed, and the electrode voltage was measured for Tests 9-1 to 9-7. In order to know the change in current density in the cation exchange membrane, the cathode was rotated on the cation exchange membrane surface for Tests 9-1 to 9-7, and the change in electrolysis voltage was measured. The results are shown in Table 9. For all cathodes in Tests 9-1 to 9-7, the electrolysis voltage did not change even when the cathode was rotated, and it was found that there was almost no change in the electrical resistance in the cation exchange membrane. However, when the nickel wire diameter was 0.05 mm, it was found that the electrolysis voltage rose, possibly due to the small cathode surface area. In addition, when the wire diameter was 0.18 mm, the voltage rose, although the cause is unknown. There appears to be a problem with the wire diameter and the gap between the wires, and it was found that this also caused the voltage to rise and was not practical.
[0121] [Table 9]
[0122] In the present embodiment, the current density distribution in the cation exchange membrane, which has rarely been discussed in the past and is a cause of large electrical resistance, can be kept almost uniform, and a low electrolysis voltage can be maintained. Furthermore, in long-term operation, the load in the cation exchange membrane is made uniform over the entire surface, which results in no uneven load and a longer life. In addition, in Tables 4, 5, and 9, Test Nos. 3-2 to 3-5, 4-1 to 4-3, and 9-6, which are indicated as "Examples", are "Reference Examples". [Industrial Applicability]
[0123] The electrolytic cell of the present invention is a so-called zero-gap type cation exchange membrane process chloralkali electrolytic cell that can obtain a lower electrolysis voltage and substantially eliminates current bias in the cation exchange membrane, thereby contributing to extending the life of expensive cation exchange membranes. [Explanation of symbols]
[0124] 1 electrode 2. Cation exchange membrane 3 Flow of generated bubbles 10 Anode 11 Cathode 12 Cation exchange membrane 13 Cathode Chamber 14 Anode chamber 15 Elastic Body 16 Cathode assembly 17,18 Ribs 19,20 Liquid hole
Claims
1. A cation exchange membrane serving as a diaphragm; an anode in intimate contact with one surface of the cation exchange membrane; an anode chamber in which the anode is accommodated and filled with an anolyte; a cathode in intimate contact with the other surface of the cation exchange membrane; a cathode chamber in which the cathode is accommodated and which is filled with a catholyte; In a zero-gap type cation exchange membrane process sodium chloride electrolysis cell, an anode gas is generated at the anode and hydrogen is generated at the cathode, the anode has an electrode substrate made of a porous plate and an anode coating layer made of a hydrophilic electrode active material formed on a surface of the electrode substrate; The electrode base material is a roll-pressed product of an expanded metal having a plate thickness of t mm, a long side opening period of LW mm, a short side opening period of SW mm, and a strand of W mm, The opening ratio of the expanded metal is 20% or more and 60% or less, The ratio calculated by LW / SW is 1.5 or more and 3.5 or less, The plate thickness t of the porous plate is 0.5 mm or more and 0.8 mm or less, The opening period SW of the short side is 2.0 mm or more and 5.5 mm or less, The apparent thickness (Pmm) of the roll-pressed product is 1.1t or more and 2.0t or less, The cathode has a nickel mesh formed by plain weaving nickel wires having a wire diameter of 0.06 to 0.14 mm, and a cathode coating layer made of a hydrophilic electrode active material formed on a surface of the nickel mesh, The pitch of the cathode is equal to or greater than (0.64 / 2.2) and equal to or less than 1 / 2 of the SW of the anode, The zero-gap type cation exchange membrane process sodium chloride electrolysis cell is characterized in that it has an elastic body that applies pressure to the surface of the cathode opposite to the surface that is in close contact with the cation exchange membrane.
2. The expanded metal is made of pure titanium, the anolyte is a saline solution; the catholyte is an aqueous caustic soda solution; Chlorine gas is produced as the anode gas, and 2. The zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to claim 1, wherein caustic soda and hydrogen are produced in the cathode chamber.
3. The expanded metal is made of pure titanium, and 3. The zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to claim 1, wherein the electrode active material of the anode coating layer is a hydrophilic composite oxide containing iridium, ruthenium and titanium.
4. 3. The zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to claim 1, wherein the electrode active material of the cathode coating layer contains a platinum group metal and / or a platinum group metal oxide.
5. 3. The zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to claim 1, wherein the electrode active material of the cathode coating layer contains a composite oxide of ruthenium and cerium.
6. 3. The zero-gap type cation exchange membrane process sodium chloride electrolysis cell according to claim 1, wherein the pitch of the nickel mesh is 0.6 to 1.2 mm.
7. 3. The zero-gap type cation exchange membrane process saline electrolysis cell according to claim 1 or 2, characterized in that the elastic body is a sponge-like mattress made of nickel wire randomly folded and bundled, and is placed between the current collector and the cathode.
8. A zero-gap type cation exchange membrane method salt electrolysis cell as described in claim 1 or 2, characterized in that the anode further has an anode coating layer of hydrophobic electrode active material between the surface of the electrode substrate and the anode coating layer of the hydrophilic electrode active material.
Citation Information
Patent Citations
Electrolysis method for alkali chloride using cation exchange membrane
JP1981146884A
Electrolytic method
JP1983130286A
Reactivation method of electrode for electrolysis
JP1992032594A
Laminate
JP2018159129A
Bipolar zero-gap electrolytic cell
JP4453973B2
Cited By
Novel integrally-formed V-shaped chamber multi-piece electrolytic cell
CN120485803A